Corrigendum to ‘A U.S. scientific community review of carbon cycle science gaps and opportunities to better support earth system science and carbon management’ [Earth-Science Reviews 278 (2026) 1-28] - N.C. Parazoo; D. Carroll; J.B. Abshire; Y.M. Bar-On; R.A. Birdsey; A.A. Bloom; K.W. Bowman; R.K. Braghiere; L.M. Bruhwiler; B. Byrne; A. Chatterjee; D. Crisp; et al. (Earth-Science Reviews, 2026)

Antisense oligonucleotide-mediated disruption of mRNA localisation inhibits angiogenesis - Josy Augustine; Precious O. Owuamalam; Jennifer Nicell; Peter Barabas; Susanta Chatterjee; Michael O’Hare; Tim M. Curtis; Guilherme Costa (Angiogenesis, 2026)
mRNA localisation is a critical posttranscriptional mechanism that confers a spatiotemporal dimension to the control of gene expression. Among diverse outcomes, this process can result in compartmentalised protein synthesis and consequently, elicit localised cellular responses. Targeting mRNAs to their destination is often determined by localisation elements (LEs) contained in untranslated regions within targeted transcripts. Although mRNA localisation has been widely explored in the context of subcellular biology, its roles in tissue function are only just beginning to emerge. A defined set of transcripts accumulate at the leading edge of endothelial tip cells that guide emerging vessels during sprouting angiogenesis. This includes RAB13 and NET1 mRNAs, which encode proteins implicated in cytoskeletal remodelling processes underpinning cell motility. In this study, we tested the anti-angiogenic potential of antisense oligonucleotide (ASO)-based strategies designed to perturb RAB13 and NET1 localisation. Upon confirming that ASOs targeting LEs mislocalise these mRNAs without altering steady-state levels of the encoded proteins, we applied them to a series of in vitro, ex vivo and in vivo angiogenesis assays. Remarkably, the mislocalisation of RAB13 and NET1 inhibits chemotaxis and vessel sprouting in response to pro-angiogenic stimuli. Furthermore, vessel sprouting from mouse choroidal explants and retinal angiogenesis are also hindered by mRNA mislocalisation. Altogether, our strategy for disrupting spatial control of gene expression in endothelial cells opens new mechanistic avenues for the manipulation of vessel formation.

Microplastic contamination across different feeding guilds of commercially important fishes from the Southeast Coast of India - Tejaswini Singh; Neha Kangujam; Suchitra Chanu Sanabam; Saoo Wan Emi Phyllei; S. M. Sundarapandian; K. Sivakumar; Subhankar Chatterjee (Environmental Monitoring and Assessment, 2026)

A U.S. scientific community review of carbon cycle science gaps and opportunities to better support earth system science and carbon management - N.C. Parazoo; D. Carroll; J.B. Abshire; Y.M. Bar-On; R.A. Birdsey; A.A. Bloom; K.W. Bowman; R.K. Braghiere; L.M. Bruhwiler; B. Byrne; A. Chatterjee; D. Crisp; et al. (Earth-Science Reviews, 2026)

Saroglitazar, a novel PPAR-α/γ agonist, modulates thyroid hormone homeostasis through hepatic UGT expression in wistar rats - Praveen Kumar Jain; Laxit K. Bhatt; Ashvin K. Patel; Satyam Patel; Kalpesh Z. Patani; Rajesh J. Patel; Pankaj Dwivedi; Shekhar B. Kadam; Ramchandra K. Ranvir; Hiren M. Patel; Abhijit Chatterjee; Laxmikant Gupta; et al. (Chemico-Biological Interactions, 2026)

Performance assessment of transformer-based model for Sea Surface Temperature Prediction in the Indian Ocean Region - D. Sathya Narayanan; B. Sheela Rani; N.R. Krishnamoorthy; M. Roja Raman; V. Kalyan; Aneesh A. Lotliker; Abhisek Chatterjee (Regional Studies in Marine Science, 2026)

Spatiotemporal evolution of the quartzofeldspathic gneisses of the Vinjamuru domain, Eastern Ghats Belt, India: Implications for the late Paleoproterozoic crustal growth in a craton-margin orogenic belt - Amitava Chatterjee; Suresh C. Patel; Chang Whan Oh; Janisar M. Sheikh (Lithos, 2026)

Azolla additives in traditional vegetable waste-cattle manure reshape the niche microbiome dynamics and orchestrate context-dependent biodegradation and nutrient cycling - Argha Chakraborty; Saroja M. K.; Adrija Banerjee; Sukamal Sarkar; Monidipta Saha; Bhubaneswar Pradhan; Natesan Ravisankar; Gautam Chatterjee (Journal of Environmental Chemical Engineering, 2026)

Potential contribution of Barents–Kara Sea ice loss to the increased rainfall over northwest India through atmospheric teleconnection - Sourav Chatterjee; Doug M Smith; Nuncio Murukesh; M. Ravichandran (Climate Dynamics, 2026)

Fungi-assisted bio-flocculation for microalgae harvesting: Literature-guided optimization and experimental evaluation using Aspergillus awamori - Jesna Fathima; Ajesh M. Arjun; Pritha Chatterjee (Biocatalysis and Agricultural Biotechnology, 2026)

Deep learning for sea surface temperature prediction in the Indian Ocean: A comparative study using 1D-CNN, LSTM, 1DCNN-LSTM and attention based 1DCNN-LSTM architectures - B. Sheela Rani; D. Sathya Narayanan; M.B. Salma Jasmine; N.R. Krishnamoorthy; M. Roja Raman; Aneesh A. Lotliker; Abhisek Chatterjee (Dynamics of Atmospheres and Oceans, 2026)

What moves the user? Multi-domain motivations behind window and blinds interactions from a user perspective in open-plan offices - Verena M. Barthelmes; Caroline Karmann; Viviana Gonzalez Serrano; Arnab Chatterjee; Kun Lyu; Jan Wienold; Marilyne Andersen; Dusan Licina; Dolaana Khovalyg (Building and Environment, 2026)

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Wurtzite ZnO nanoflower carbon composite for cationic dye adsorption, phytotoxicity study, and industrial wastewater remediation - M. Bhavani Lakshmi; Alibasha Akbar; Tanmay Chatterjee; Archana V.; Quazi Arif Islam; Mihir Ghosh (Journal of Water Process Engineering, 2026)

Neoarchean crustal evolution in the Madras Block: Geochemical and petrological evidence from felsic gneiss and amphibolite - P.V. Thanooja; K. Sajeev; M. Satish-Kumar; I.S. Williams; T. Takahashi; C. Chatterjee (Polar Science, 2025)

Magnetically recoverable biogenic CuFe2O4 nanoparticles for sustainable catalytic degradation of organic dyes - Alibasha Akbar; Bhavani Lakshmi M; Ankur Howlader; Archana V; Quazi Arif Islam; Tanmay Chatterjee; Mihir Ghosh (Journal of Water Process Engineering, 2025)

P22-27 High-Content Screening in C. elegans using SydLab™One for Neuronanosafety: Impacts of Silver Nanoparticles on Neurodegeneration - N. Chatterjee; M. Pierron; L. Mouchiroud (Toxicology Letters, 2025)

Uncovering microbial drivers and regulatory edaphic factors for DNRA-nitrogen recovery under diverse rice agro-ecosystems - Megha Kaviraj; Upendra Kumar; S. N. Chatterjee; M. Shahid; A. K. Nayak (Plant and Soil, 2025)

Spatial Heterogeneity in Health Risk Assessment of Heavy Metals During North-East Monsoon and South-West Monsoon over India - Martina Rani; Sakshi Ahlawat; N. Vijayan; Lokesh Yadav; Tirthankar Banerjee; Abhijeet Chatterjee; Manpreet Singh Bhatti; Trupti Das; Amit Dhir; Sangita Goel; Altaf Husain Khan; Ravindra Khaiwal; et al. (Aerosol Science and Engineering, 2025)

Colonoscopy findings in CDH1 carriers from a multicenter international study - Arjun Chatterjee; Robert Hüneburg; Qijun Yang; Shannon Morrison; Anna Bettzüge; Tim Marwitz; Stefan Aretz; Isabel Spier; Tim Ripperger; Silke Redler; Mykyta Kachanov; Alexander E. Volk; et al. (Familial Cancer, 2025)
Germline (likely-)pathogenic variants (PV) in CDH1 predispose carriers to hereditary diffuse gastric cancer and lobular breast cancer. Previous studies from the United States suggest CDH1 variant carriers have an increased risk for adenomas or sessile serrated lesions (SSL), yet data linking CDH1 PVs and colorectal neoplasia are scarce. We aimed to investigate colonoscopy findings in CDH1 PVs. Adults carrying a PV/LPV in CDH1 with ≥ 1 colonoscopy between 01/01/2004–12/31/2023 were included. Patients were sourced from the David G. Jagelman Inherited Colorectal Cancer Registries at Cleveland Clinic and the German Consortium for Familial Intestinal Cancer. 103 CDH1 PV carriers were included. Most were female (66%) and white (93.1%). The median age at first colonoscopy was 47 years. The adenoma detection rate (ADR) was 29.4% (95% CI:19.9–41.1%) in the German cohort and 48.6% (95% CI: 33.0-64.4%) in the Cleveland cohort ( p = 0.055) and significantly correlated with age (< 45 years, 13.6% (95% CI: 6.40–26.7%); 45–49 years, 52.4% (95% CI: 32.4–71.7%); ≥50 years, 52.6% (95% CI: 37.3–67.5%); p < 0.001). The ADR in Cleveland was higher than the U.S. average ADR but the difference was not statistically significant (48.6% vs. 35.6%, p = 0.08), and the ADR in the German cohort (29.4%) was similar to the national German average risk screening cohort (31.3% in men, p = 0.84; 20.1% in women, p = 0.08). In our screening cohort with CDH1 PV carriers, we demonstrated an ADR of 13.5% in individuals under 45 years, similar to the ADR in patients aged 25–40 years with a family history of CRC. Overall, SSL detection rate was 9.7%. Colorectal cancer was diagnosed in 3 patients (3.2%), 2/3 with an early age of onset before the age of 50 years. This first international study provides preliminary evidence of a higher ADR in U.S. CDH1 PV carriers compared to the general population, with a high number of adenomas detected before the age of 50. This may indicate an increased CRC risk that should be explored in larger studies.

Modified emission and scaling factors for methane and nitrous oxide in rice system of India: A country specific disaggregate approach - Pratap Bhattacharyya; A. Bhatia; N. Jain; D. Chatterjee; S. Mohanty; M. Prabhakar; Pratibha M; N.N. Jambhulkar; S. Ananthakrishnan; S.K. Nayak; A.K. Nayak; H. Pathak (Journal of Environmental Management, 2025)

Identifying differential survival, photolocomotor behavior, and gene expression responses to cylindrospermopsin in Danio rerio and Pimephales promelas - Kendall R. Scarlett; Laura M. Langan; Lea M. Lovin; Abigail N. Henke; Sujin Kim; Kevin M. Stroski; C. Kevin Chambliss; Saurabh Chatterjee; J. Thad Scott; Bryan W. Brooks (Science of The Total Environment, 2025)

Microplastic contamination and environmental risks in the Beas River, western Himalayas - Ritindra N. Bhaduri; Sougata Sinha; Angelina M. Guererro; Sonja L. Jackson; Elvin A. Alemán; Subhankar Chatterjee (Environmental Pollution, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Navigating the threat of African swine fever: a comprehensive review - Keya Mahanta; Bushra Jabeen; Ranjita Chatterjee; Rafiqul M. Amin; Jyotishree Bayan; Sourabh Sulabh (Tropical Animal Health and Production, 2024)

Sophorolipid: An Effective Biomolecule for Targeting Microbial Biofilms - Sunidhi Dhadwal; Shristi Handa; Mary Chatterjee; Ibrahim M. Banat (Current Microbiology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Expanding Policies to Support Culturally Tailored Nutrition Care for Diverse Older Adults and Their Family Caregivers - L. Gutierrez Munoz; S. Shrivastava; S. Arevalo; M. Karkare; S. Chatterjee; Y. Caraballo Lopez; S. Ranjan; A. Hinojosa; M. Vishwanathan; S. Jacobo; M. Barragan; M. Raj (Journal of the Academy of Nutrition and Dietetics, 2024)

Anisotropy of magnetic susceptibility and rock magnetism of high-grade rocks from Eastern Ghats Mobile Belt, India: Constraints to tectonics - Solanky Das; M Venkateshwarlu; Supriya Mondal; Saurodeep Chatterjee; Debesh Gain (Journal of Earth System Science, 2024)

Investigating the use of network analysis metrics to benchmark Industrial Symbiosis development - Abheek Chatterjee; Oren Minsk; Matthew J. Triebe; Buddhika M. Hapuwatte; Daniel Kietzer; Sushma Kittali-Weidner; K.C. Morris; Nehika Mathur (Journal of Cleaner Production, 2024)

Corrigendum to “Cation exchange to montmorillonite induces selective adsorption of amino acids” [Geochim. Cosmochim. Acta 372 (2024) 181–195] - Emily Millman; Anamika Chatterjee; Kimberly M. Parker; Jeffrey G. Catalano (Geochimica et Cosmochimica Acta, 2024)

Low Mo mobility during the laterization of ultramafic bedrock: Evidence from the East Sulawesi Ophiolite, Indonesia - Adrianus Damanik; Martin Wille; Qasid Ahmad; Sukalpa Chatterjee; Sean A. Crowe; Kohen W. Bauer; Martin Grosjean; Sri Yudawati Cahyarini; Satria Bijaksana; James M. Russell; Hendrik Vogel (Chemical Geology, 2024)

Total CO2 budget estimate and degassing dynamics for an active stratovolcano: Turrialba Volcano, Costa Rica - Kate M. Nelson; Christofer Jiménez; Chad D. Deering; Maarten J. de Moor; Joshua M. Blackstock; Stephen P. Broccardo; Florian M. Schwandner; Joshua B. Fisher; Snehamoy Chatterjee; Guillermo Alvarado Induni; Alejandro Rodriguez; Doménicca Guillén Pachacama; et al. (Journal of Volcanology and Geothermal Research, 2024)

Cation exchange to montmorillonite induces selective adsorption of amino acids - Emily Millman; Anamika Chatterjee; Kimberly M. Parker; Jeffrey G. Catalano (Geochimica et Cosmochimica Acta, 2024)

Reducing the environmental impact of rice production in subtropical India by minimising reactive nitrogen loss - Dibyendu Chatterjee; Saikat Ranjan Das; Sangita Mohanty; Baishnab Charan Muduli; Arti Bhatia; Bitish Kumar Nayak; Robert M. Rees; Julia Drewer; Amaresh Kumar Nayak; Tapan Kumar Adhya; Chidambaranathan Parameswaran; Jitendriya Meher; et al. (Journal of Environmental Management, 2024)

Climate change and anthropogenic pressure on Bintan Islands, Indonesia: An assessment of the policies proposed by local authorities - Martiwi Diah Setiawati; Muhammad Rizki Nandika; Indarto Happy Supriyadi; Marindah Yulia Iswari; Bayu Prayudha; Sam Wouthuyzen; Novi Susetyo Adi; Yudha Setiawan Djamil; Nuraini Rahma Hanifa; Uday Chatterjee; Aidy M. Muslim; Tsuyoshi Eguchi (Regional Studies in Marine Science, 2023)

Interpretation of deformation microstructures in syntectonic granite: insights from Phulad granite, Rajasthan, NW India - Ayan Kumar Sarkar; Anirban Manna; Sadhana M. Chatterjee; Alip Roy (Geosciences Journal, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Characteristics of mean and extreme precipitation in Ny Ålesund, Arctic - R. Athulya; M. Nuncio; Sourav Chatterjee; P.J. Vidya (Atmospheric Research, 2023)

Fuzzy logic, geostatistics, and multiple linear models to evaluate irrigation metrics and their influencing factors in a drought-prone agricultural region - S.M. Rabbi Al Zihad; Abu Reza Md Towfiqul Islam; Md Abu Bakar Siddique; Md Yousuf Mia; Md Saiful Islam; Md Aminul Islam; A.B.M. Mainul Bari; Md Bodrud-Doza; Sobhy M. Yakout; Venkatramanan Senapathi; Sumanta Chatterjee (Environmental Research, 2023)

Energy, SBS symptoms, and productivity in Swiss open-space offices: Economic evaluation of standard, actual, and optimum scenarios - Dolaana Khovalyg; Cecile A. Berquand; Giulia Vergerio; Verena M. Barthelmes; Arnab Chatterjee; Cristina Becchio; Dusan Licina (Building and Environment, 2023)

Hails in Ny Alesund, Svalbard-atmospheric vertical structure and dependence on circulation - M. Nuncio; R. Athulya; Naveen Nandanan; Sourav Chatterjee; K. Satheesan; Asutosh Acharya; M. P. Subeesh; P. J. Vidya (Natural Hazards, 2023)
Hails observed at Ny Alesund, Svalbard in the Arctic during December–February 2018–19 is examined along with the atmospheric circulation patterns. When hail was noticed, surface warming and southwesterly—westerly winds were noticed. Atmospheric circulation pattern was characterised by high pressure anomaly over northwestern Europe. High clouds as well as excess liquid water were present when the high pressure systems were active over northwestern Europe. This is because winds blowing over ocean collect more moisture as well as transport nucleating particles to Svalbard. Also, hourly winds from ERA 5 reanalysis indicated vertical shear required for hail formation. When hails were observed, mixed precipitation types were recorded with the maximum intensities arising from the hails. The West Spitzbergen Current (WSC) induces a strong east west sea surface temperature (SST) gradient in the ocean west of Svalbard. A corresponding gradient in the atmospheric temperature is also maintained by the WSC in the west to east direction in the lower atmosphere. Moisture laden westerlies cross the SST gradient and induce strong frontal activity in the lower atmosphere resulting intense precipitation and hail. The upward vertical velocity noted in the lower troposphere supports the frontal activity. Human activities in the Arctic as elsewhere are bound to increase. Hence, there is a need to study the intense precipitation in the Arctic as well as its reasons as it can impact the Arctic environment and human activity. This calls for more continuous observations to clearly identify mechanisms and frequency of intense precipitation in the Arctic.

Halogen enrichment in the North American lithospheric mantle from the dehydration of the Farallon plate - George Segee-Wright; Jaime D. Barnes; John C. Lassiter; Duncan J. Holmes; Grace M. Beaudoin; Rudra Chatterjee; Daniel F. Stockli; J. Elis Hoffmann; Timm John (Geochimica et Cosmochimica Acta, 2023)

Agronomic manipulation in main season and ratoon rice influences growth, productivity, and regeneration ability in tropical lowlands - B. Lal; Priyanka Gautam; A.K. Nayak; R. Raja; B.B. Panda; R. Tripathi; M. Shahid; D. Chatterjee; P. Bhattacharyya; P. Bihari; Teekam Singh; S.K. Meena; et al. (Field Crops Research, 2023)

Effect of exogenous fibrolytic enzymes supplementation on voluntary intake, availability of nutrients and growth performance in Black Bengal kids (Capra hircus) - Manoj Kumar; A. Chatterjee; T.K. Dutta; Yora Reena; Asif Mohammad; C. Bhakat; Saroj Rai; D.K. Mandal; M. Karunakaran (Small Ruminant Research, 2023)

Novel post-acquisition image processing to attenuate red blood cell autofluorescence for quantitative image analysis - Nicole A. Bouffard; Kyra Lee; Nicole M. DeLance; Todd Clason; Nimrat Chatterjee; Douglas J. Taatjes (Histochemistry and Cell Biology, 2023)

Prostate cancer addiction to oxidative stress defines sensitivity to anti-tumor neutrophils - Diane L. Costanzo-Garvey; Adam J. Case; Gabrielle F. Watson; Massar Alsamraae; Arpita Chatterjee; Rebecca E. Oberley-Deegan; Samikshan Dutta; Maher Y. Abdalla; Tammy Kielian; Merry L. Lindsey; Leah M. Cook (Clinical & Experimental Metastasis, 2022)
Bone metastatic prostate cancer (BM-PCa) remains one of the most difficult cancers to treat due to the complex interactions of cancer and stromal cells. We previously showed that bone marrow neutrophils elicit an anti-tumor immune response against BM-PCa. Further, we demonstrated that BM-PCa induces neutrophil oxidative burst, which has previously been identified to promote primary tumor growth of other cancers, and a goal of this study was to define the importance of neutrophil oxidative burst in BM-PCa. To do this, we first examined the impact of depletion of reactive oxygen species (ROS), via systemic deletion of the main source of ROS in phagocytes, NADPH oxidase (Nox)2, which we found to suppress prostate tumor growth in bone. Further, using pharmacologic ROS inhibitors and Nox2-null neutrophils, we found that ROS depletion specifically suppresses growth of androgen-insensitive prostate cancer cells. Upon closer examination using bulk RNA sequencing analysis, we identified that metastatic prostate cancer induces neutrophil transcriptomic changes that activates pathways associated with response to oxidative stress. In tandem, prostate cancer cells resist neutrophil anti-tumor response via extracellular (i.e., regulation of neutrophils) and intracellular alterations of glutathione synthesis, the most potent cellular antioxidant. These findings demonstrate that BM-PCa thrive under oxidative stress conditions and such that regulation of ROS and glutathione programming could be leveraged for targeting of BM-PCa progression.

Mineral magnetic and geochemical characterization of the dust and soils around Mejia Thermal Power Plant, West Bengal: Implications to source apportionment - Rimjhim Maity; M Venkateshwarlu; Supriya Mondal; M R Kapawar; Debesh Gain; Saurodeep Chatterjee; Punyotoya Paul (Journal of Earth System Science, 2022)

Modelling the Spatial Variation of Methane and Nitrous Oxide Emission from Rice Fields Using DNDC Model - Rahul Tripathi; M. Majhi; S. G. Sahu; S. Mohanty; K. C. Moharana; Md Shahid; C. K. Swain; B. Lal; P. Gautam; P. K. Dash; D. Chatterjee; A. Kumar; et al. (Journal of the Indian Society of Remote Sensing, 2021)

Are ocean-moored buoys redundant for prediction of Indian monsoon? - Maheswar Pradhan; Ankur Srivastava; Suryachandra A. Rao; Deep Sankar Banerjee; Abhisek Chatterjee; P. A. Francis; O. P. Sreejith; M. Das Gupta; V. S. Prasad (Meteorology and Atmospheric Physics, 2021)

Seasonal dynamics of plant pollinator networks in agricultural landscapes: how important is connector species identity in the network? - Pushan Chakraborty; Soumik Chatterjee; Barbara M. Smith; Parthiba Basu (Oecologia, 2021)

Assessment of groundwater depletion–induced land subsidence and characterisation of damaging cracks on houses: a case study in Mohali-Chandigarh area, India - Neha Kadiyan; R. S. Chatterjee; Pranshu Pranjal; Pankaj Agrawal; S. K. Jain; M. L. Angurala; A. K. Biyani; M. S. Sati; Dheeraj Kumar; Ashutosh Bhardwaj; P. K. Champati Ray (Bulletin of Engineering Geology and the Environment, 2021)

Backyard poultry farming for sustained production and enhanced nutritional and livelihood security with special reference to India: a review - U. Rajkumar; S. V. Rama Rao; M. V. L. N. Raju; R. N. Chatterjee (Tropical Animal Health and Production, 2021)

Effect of reducing energy intake during the dry period on milk production, udder health, and body condition score of Jersey crossbred cows in the tropical lower Gangetic region - Amit Kumar Singh; Champak Bhakat; D. K. Mandal; A. Mandal; S. Rai; A. Chatterjee; M. K. Ghosh (Tropical Animal Health and Production, 2020)

Characterization of phenazine-1-carboxylic acid by Klebsiella sp. NP-C49 from the coral environment in Gulf of Kutch, India - Neha P. Patel; M. Raju; Soumya Haldar; Pabitra B. Chatterjee (Archives of Microbiology, 2020)

Proceedings of the fourth international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Christine B. Ambrosone; Reiko Nishihara; Hugo J. W. L. Aerts; Melissa Bondy; Nilanjan Chatterjee; Montserrat Garcia-Closas; Marios Giannakis; Jeffrey A. Golden; Yujing J. Heng; N. Sertac Kip; Jill Koshiol; et al. (Cancer Causes & Control, 2019)

Inter-relationship between intercepted radiation and rice yield influenced by transplanting time, method, and variety - Priyanka Gautam; B. Lal; A. K. Nayak; R. Raja; B. B. Panda; R. Tripathi; M. Shahid; U. Kumar; M. J. Baig; D. Chatterjee; C. K. Swain (International Journal of Biometeorology, 2019)

Wyrtki Jets: Role of intraseasonal forcing - S Prerna; Abhisek Chatterjee; A Mukherjee; M Ravichandran; S S C Shenoi (Journal of Earth System Science, 2019)

Comparing a Statistical Model and Bayesian Approach to Establish the Design Space for the Coating of Ciprofloxacin HCl Beads at Different Scales of Production - Bhaveshkumar H. Kothari; Raafat Fahmy; H. Gregg Claycamp; Christine M. V. Moore; Sharmista Chatterjee; Stephen W. Hoag (AAPS PharmSciTech, 2018)

Measuring potassium fractions is not sufficient to assess the long-term impact of fertilization and manuring on soil’s potassium supplying capacity - Debarup Das; Amaresh Kumar Nayak; V. K. Thilagam; Dibyendu Chatterjee; M. Shahid; Rahul Tripathi; S. Mohanty; Anjani Kumar; B. Lal; Priyanka Gautam; B. B. Panda; S. S. Biswas (Journal of Soils and Sediments, 2018)

Mortality associated with candidemia in non-neutropenic cancer patients is not less compared to a neutropenic cohort of cancer patients - G. Goel; M. Chandy; A. Bhattacharyya; S. Banerjee; S. Chatterjee; S. Mullick; S. Sinha; K. Sengupta; K. Dhar; S. Bhattacharya; S. Rudramurthy; A. Chakrabarti (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

A Systematic Review on Bioelectrochemical Systems Research - M. M. Ghangrekar; Pritha Chatterjee (Current Pollution Reports, 2017)

Time dependent pharmacokinetics of pembrolizumab in patients with solid tumor and its correlation with best overall response - Hongshan Li; Jingyu Yu; Chao Liu; Jiang Liu; Sriram Subramaniam; Hong Zhao; Gideon M. Blumenthal; David C. Turner; Claire Li; Malidi Ahamadi; Rik de Greef; Manash Chatterjee; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

ENSO related SST anomalies and relation with surface heat fluxes over south Pacific and Atlantic - S. Chatterjee; M. Nuncio; K. Satheesan (Climate Dynamics, 2017)

Groundwater arsenic contamination and its health effects in India - Dipankar Chakraborti; Mohammad Mahmudur Rahman; Bhaskar Das; Amit Chatterjee; Dipankar Das; Biswajit Nayak; Arup Pal; Uttam Kumar Chowdhury; Sad Ahmed; Bhajan Kumar Biswas; Mrinal Kumar Sengupta; Md. Amir Hossain; et al. (Hydrogeology Journal, 2017)

Evidence for the existence of Persian Gulf Water and Red Sea Water in the Bay of Bengal - Vineet Jain; D. Shankar; P. N. Vinayachandran; A. Kankonkar; Abhisek Chatterjee; P. Amol; A. M. Almeida; G. S. Michael; A. Mukherjee; Meenakshi Chatterjee; R. Fernandes; R. Luis; et al. (Climate Dynamics, 2017)

A Systematic Approach of Employing Quality by Design Principles: Risk Assessment and Design of Experiments to Demonstrate Process Understanding and Identify the Critical Process Parameters for Coating of the Ethylcellulose Pseudolatex Dispersion Using Non-Conventional Fluid Bed Process - Bhaveshkumar H. Kothari; Raafat Fahmy; H. Gregg Claycamp; Christine M. V. Moore; Sharmista Chatterjee; Stephen W. Hoag (AAPS PharmSciTech, 2017)

Reaction enhanced channelised fluid-flux along mid- crustal shear zone: An example from Mesoproterozoic Phulad Shear Zone, Rajasthan, India - Sadhana M Chatterjee; Manideepa Roy Choudhury; Subhrajyoti Das (Journal of Earth System Science, 2016)

Spatio-temporal variation in chemical characteristics of PM10 over Indo Gangetic Plain of India - S. K. Sharma; T. K. Mandal; M. K. Srivastava; A. Chatterjee; Srishti Jain; M. Saxena; B. P. Singh; Saraswati; A. Sharma; A. Adak; S. K.Ghosh (Environmental Science and Pollution Research, 2016)

Low efficiency of sewage treatment plants due to unskilled operations in India - Pritha Chatterjee; M. M. Ghangrekar; Surampalli Rao (Environmental Chemistry Letters, 2016)

Deformation of footwall rock of Phulad Shear Zone, Rajasthan: Evidence of transpressional shear zone - Manideepa Roy Choudhury; Subhrajyoti Das; Sadhana M Chatterjee; Sudipta Sengupta (Journal of Earth System Science, 2016)

Citric Acid Induced Potassium and Silicon Release in Alfisols, Vertisols and Inceptisols of India - Dibyendu Chatterjee; S. C. Datta; K. M. Manjaiah (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Fluorescence Quenching Property of C-Phycocyanin from Spirulina platensis and its Binding Efficacy with Viable Cell Components - Meenakshi B. Paswan; Meghna M. Chudasama; Madhusree Mitra; Khushbu Bhayani; Basil George; Shruti Chatterjee; Sandhya Mishra (Journal of Fluorescence, 2016)

Obesity shifts house dust mite-induced airway cellular infiltration from eosinophils to macrophages: effects of glucocorticoid treatment - J. Diaz; L. Warren; L. Helfner; X. Xue; P. K. Chatterjee; M. Gupta; M. H. Solanki; M. Esposito; V. Bonagura; C. N. Metz (Immunologic Research, 2015)

Variation of Stable Carbon and Nitrogen Isotopic Composition of PM10 at Urban Sites of Indo Gangetic Plain (IGP) of India - S. K. Sharma; T. K. Mandal; D. M. Shenoy; Pratirupa Bardhan; Manoj K. Srivastava; A. Chatterjee; Mohit Saxena; Saraswati; B. P. Singh; S. K. Ghosh (Bulletin of Environmental Contamination and Toxicology, 2015)

Measurement of Vanadium Emissions from SCR Catalysts by ICP-OES: Method Development and First Results - T. J. Schildhauer; M. Elsener; J. Moser; I. Begsteiger; D. Chatterjee; K. Rusch; O. Kröcher (Emission Control Science and Technology, 2015)

Modernizing Pharmaceutical Manufacturing: from Batch to Continuous Production - Sau L. Lee; Thomas F. O’Connor; Xiaochuan Yang; Celia N. Cruz; Sharmista Chatterjee; Rapti D. Madurawe; Christine M. V. Moore; Lawrence X. Yu; Janet Woodcock (Journal of Pharmaceutical Innovation, 2015)

Proceedings of the second international molecular pathological epidemiology (MPE) meeting - Shuji Ogino; Peter T. Campbell; Reiko Nishihara; Amanda I. Phipps; Andrew H. Beck; Mark E. Sherman; Andrew T. Chan; Melissa A. Troester; Adam J. Bass; Kathryn C. Fitzgerald; Rafael A. Irizarry; Karl T. Kelsey; et al. (Cancer Causes & Control, 2015)

Intersex (ix) mutations of Drosophila melanogaster cause nonrandom cell death in genital disc and can induce tumours in genitals in response to decapentaplegic (dpp disk ) mutations - R. N. CHATTERJEE; P. CHATTERJEE; S. KUTHE; M. ACHARYYA-ARI; R. CHATTERJEE (Journal of Genetics, 2015)

Interaction of NO x Reduction and Soot Oxidation in a DPF with Cu-Zeolite SCR Coating - E. Tronconi; I. Nova; F. Marchitti; G. Koltsakis; D. Karamitros; B. Maletic; N. Markert; D. Chatterjee; M. Hehle (Emission Control Science and Technology, 2015)

Tipping off endothelial tubes: nitric oxide drives tip cells - Mani Krishna Priya; Giriraj Sahu; David R. Soto-Pantoja; Naga Goldy; Abaya Meenakshi Sundaresan; Vivek Jadhav; T. R. Barathkumar; Uttara Saran; B. M. Jaffar Ali; David D. Roberts; Amal Kanti Bera; Suvro Chatterjee (Angiogenesis, 2015)

A Prospective Analysis of Co-Processed Non-Ionic Surfactants in Enhancing Permeability of a Model Hydrophilic Drug - Mohammed M. Alvi; Parnali Chatterjee (AAPS PharmSciTech, 2014)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

New Mediterranean Marine biodiversity records (June 2013) - I. SIOKOU; A.S. ATES; D. AYAS; J. BEN SOUISSI; T. CHATTERJEE; M. DIMIZA; H. DURGHAM; K. DOGRAMMATZI; D. ERGUDEN; V. GERAKARIS; M. GREGO; Y. ISSARIS; et al. (Mediterranean Marine Science, 2013)
This paper concerns records of species that have extended their distribution in the Mediterranean Sea. The finding of the rare brackish angiosperm Althenia filiformis in the island of Cyprus is interesting since its insertion in the Red Data Book of the Flora of Cyprus is suggested. The following species enriched the flora or fauna lists of the relevant countries: the red alga Sebdenia dichotoma (Greece), the hydrachnid mite Pontarachna adriatica (Slovenia), and the thalassinid Gebiacantha talismani (Turkey). Several alien species were recorded in new Mediterranean localities. The record of the burrowing goby Trypauchen vagina in the North Levantine Sea (Turkish coast), suggests the start of spreading of this Lessepsian immigrant in the Mediterranean Sea. The findings of the following species indicate the extension of their occurrence in the Mediterranean Sea: the foraminifer Amphistegina lobifera (island of Zakynthos, Greece), the medusa Cassiopea andromeda (Syria), the copepod Centropages furcatus (Aegean Sea), the decapod shrimp Melicertus hathor (island of Kastellorizo, Greece), the crab Menoethius monoceros (Gulf of Tunis), the barnacles Balanus trigonus, Megabalanus tintinnabulum, Megabalanus coccopoma and the bivalves Chama asperella, Cucurbitula cymbium (Saronikos Gulf, Greece).

Total Serum Immunoglobulin E in Children with Asthma - M. Lama; M. Chatterjee; T. K. Chaudhuri (Indian Journal of Clinical Biochemistry, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Rock physics template (RPT) analysis of well logs and seismic data for lithology and fluid classification in Cambay Basin - Saurabh Datta Gupta; Rima Chatterjee; M. Y. Farooqui (International Journal of Earth Sciences, 2012)

A new atlas of temperature and salinity for the North Indian Ocean - A CHATTERJEE; D SHANKAR; S S C SHENOI; G V REDDY; G S MICHAEL; M RAVICHANDRAN; V V GOPALKRISHNA; E P RAMA RAO; T V S UDAYA BHASKAR; V N SANJEEVAN (Journal of Earth System Science, 2012)

HIV-1 Tat-Mediated Neurotoxicity in Retinal Cells - Nivedita Chatterjee; Shannon Callen; Gail M. Seigel; Shilpa J. Buch (Journal of Neuroimmune Pharmacology, 2011)

Genetic analysis of juvenile growth and carcass traits in a full diallel mating in selected colored broiler lines - Ullengala Rajkumar; R. P. Sharma; M. K. Padhi; K. S. Rajaravindra; B. L. N. Reddy; M. Niranjan; T. K. Bhattacharya; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2011)

Polymorphism in the Prolactin Promoter and Its Association with Growth Traits in Chickens - T. K. Bhattacharya; R. N. Chatterjee; R. P. Sharma; M. Niranjan; U. Rajkumar; B. L. N. Reddy (Biochemical Genetics, 2011)

Significance of the midgut bacterium Pseudomonas fluorescens on Culex vishnui (Diptera: Culicidae) larval development - M. Roy; S.N. Chatterjee; P. Roy; T.K. Dangar (International Journal of Tropical Insect Science, 2010)

Inhibitory Effects of the Divalent Metal Ions on Biomethanation by Isolated Mesophilic Methanogen in AC21 Medium in Presence or Absence of Juices from Water Hyacinth - Nilanjan Chakraborty; Manjushree Chatterjee; Gouranga M. Sarkar; Sujit Chandra Lahiri (BioEnergy Research, 2010)

Effect of stocking density and journey length on the welfare of rohu (Labeo rohita Hamilton) fry - N. Chatterjee; A. K. Pal; T. Das; R. Dalvi; M. S. Mohammad; K. Sarma; S. C. Mukherjee; K. Baruah (Aquaculture International, 2010)

Quantification and Source Identification of Polycyclic Aromatic Hydrocarbons in Core Sediments from Sundarban Mangrove Wetland, India - C. Domínguez; S. K. Sarkar; A. Bhattacharya; M. Chatterjee; B. D. Bhattacharya; E. Jover; J. Albaigés; J. M. Bayona; Md. A. Alam; K. K. Satpathy (Archives of Environmental Contamination and Toxicology, 2010)

Microalbuminuria: An inexpensive, non invasive bedside tool to predict outcome in critically ill patients - Surupa Basu; S. Chaudhuri; M. Bhattacharyya; T. K. Chatterjee; S. Todi; A. Majumdar (Indian Journal of Clinical Biochemistry, 2010)

Acid leachable trace metals in sediment cores from Sunderban Mangrove Wetland, India: an approach towards regular monitoring - M. P. Jonathan; S. K. Sarkar; P. D. Roy; Md. A. Alam; M. Chatterjee; B. D. Bhattacharya; A. Bhattacharya; K. K. Satpathy (Ecotoxicology, 2010)

Polycyclic Aromatic Hydrocarbons in Intertidal Marine Bivalves of Sunderban Mangrove Wetland, India: An Approach to Bioindicator Species - O. Zuloaga; A. Prieto; A. Usobiaga; S. K. Sarkar; M. Chatterjee; B. D. Bhattacharya; A. Bhattacharya; Md. A. Alam; K. K. Satpathy (Water, Air, & Soil Pollution, 2009)

When we enhance cognition with Adderall, do we sacrifice creativity? A preliminary study - Martha J. Farah; Caroline Haimm; Geena Sankoorikal; M. Elizabeth Smith; Anjan Chatterjee (Psychopharmacology, 2009)

Organochlorine Pesticide Residues in Sediment Cores of Sunderban Wetland, Northeastern Part of Bay of Bengal, India, and Their Ecotoxicological Significance - S. K. Sarkar; A. Binelli; C. Riva; M. Parolini; M. Chatterjee; A. K. Bhattacharya; B. D. Bhattacharya; K. K. Satpathy (Archives of Environmental Contamination and Toxicology, 2008)

An Assessment of Mercury Loading in Core Sediments of Sunderban Mangrove Wetland, India (A Preliminary Report) - Ž. Kwokal; S. K. Sarkar; M. Chatterjee; S. Franciskovis-Bilinski; H. Bilinski; A. Bhattacharya; B. D. Bhattacharya; Md. Aftab Alam (Bulletin of Environmental Contamination and Toxicology, 2008)

Drosophila simulans Lethal hybrid rescue mutation (Lhr) rescues inviable hybrids by restoring X chromosomal dosage compensation and causes fluctuating asymmetry of development - R. N. Chatterjee; P. Chatterjee; A. Pal; M. Pal-Bhadra (Journal of Genetics, 2007)

Genetic variation in catechol-O-methyltransferase (COMT) and obesity in the prostate, lung, colorectal, and ovarian (PLCO) cancer screening trial - Sophia S. Wang; Lindsay M. Morton; Andrew W. Bergen; Elizabeth Z. Lan; Nilanjan Chatterjee; Paul Kvale; Richard B. Hayes; Stephen J. Chanock; Neil E. Caporaso (Human Genetics, 2007)

Silica and volatile-element metasomatism of Archean mantle: a xenolith-scale example from the Kaapvaal Craton - D. R. Bell; M. Grégoire; T. L. Grove; N. Chatterjee; R. W. Carlson; P. R. Buseck (Contributions to Mineralogy and Petrology, 2005)

The effect of occlusive and unocclusive exposure to xylene and benzene on skin irritation and molecular responses in hairless rats - A. Chatterjee; R. J. Babu; E. Ahaghotu; M. Singh (Archives of Toxicology, 2005)

Formulation and Evaluation of Aerosolized Celecoxib for the Treatment of Lung Cancer - Alfred Haynes; Madhu Sudhan Shaik; Abhijit Chatterjee; M. Singh (Pharmaceutical Research, 2005)

Magnesian andesite and dacite lavas from Mt. Shasta, northern California: products of fractional crystallization of H2O-rich mantle melts - Timothy L. Grove; Michael B. Baker; Richard C. Price; Stephen W. Parman; Linda T. Elkins-Tanton; Nilanjan Chatterjee; Othmar Mntener (Contributions to Mineralogy and Petrology, 2005)

Evidence for oxidative stress in osteoarthritis - M Maneesh; H Jayalekshmi; T Suma; S Chatterjee; A Chakrabarti; T A Singh (Indian Journal of Clinical Biochemistry, 2005)

Spontaneous Colibacillosis in Infectious Bursal Disease-affected Broiler Flocks - M. Mitra; A.K. Pramanik; H.M. Bhattacharyya; D.K. Basak; A. Chatterjee; P. Roy (Tropical Animal Health and Production, 2004)

Key site variables governing the functional characteristics of Dissolved Natural Organic Matter (DNOM) in Nordic forested catchments - Bimal Chatterjee; Egil Gjessing; Jussi V. K. Kukkonen; Hkon E. Larsen; Jrg Luster; Andrea Paul; Stephan Pflugmacher; Mike Starr; Christian E. W. Steinberg; Philippe Schmitt-Kopplin; dm Zsolnay; Rolf D. Vogt; et al. (Aquatic Sciences, 2004)

Evaluation of An Aerosolized Selective COX-2 Inhibitor as a Potentiator of Doxorubicin in a Non-Small-Cell Lung Cancer Cell Line - Alfred Haynes; Madhu Sudhan Shaik; Abhijit Chatterjee; M. Singh (Pharmaceutical Research, 2003)

Fractional crystallization and mantle-melting controls on calc-alkaline differentiation trends - Timothy L. Grove; Linda T. Elkins-Tanton; Stephen W. Parman; Nilanjan Chatterjee; Othmar Mntener; Glenn A. Gaetani (Contributions to Mineralogy and Petrology, 2003)

Persistence and Effectiveness of Iprodione Against Alternaria blight in Mustard - I. Mukherjee; M. Gopal; S. C. Chatterjee (Bulletin of Environmental Contamination and Toxicology, 2003)

Modulating Action of Hyperforin on the P-Type Calcium Channels in the Membranes of Rat Cerebellar Purkinje Neurons - A. I. Fisyunov; N. A. Lozovaya; T. Sh. Tsyntsadze; N. M. Yatsenko; S. Chatterjee; O. A. Krishtal (Neurophysiology, 2001)

Bilobalide, a constituent of Ginkgo biloba, inhibits NMDA-induced phospholipase A2 activation and phospholipid breakdown in rat hippocampus - O. Weichel; M. Hilgert; S.S. Chatterjee; M. Lehr; J. Klein (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Dynamical Initialization of Boundary-Layer Data - G. K. Sen; M. Chatterjee; D. K. Sinha (Boundary-Layer Meteorology, 1998)

Lysine production byBrevibacterium linens and its mutants: Activities and regulation of enzymes of the lysine biosynthetic pathway - M. Chatterjee (Folia Microbiologica, 1998)

Mildly alkaline basalts from Pavagadh Hill, India: Deccan flood basalts with an asthenospheric origin - J. D. Greenough; K. R. Hari; A. C. Chatterjee; M. Santosh (Mineralogy and Petrology, 1998)

Production of lactic acid by direct fermentation of starchy wastes by an amylase-producing Lactobacillus - M. Chatterjee; S.L. Chakrabarty; B.D. Chattopadhyay; R.K. Mandal (Biotechnology Letters, 1997)

Minimally modified low density lipoproteins induce aortic smooth muscle cell proliferation via the activation of mitogen activated protein kinase - Chavali Balagopalakrishna; Anil K. Bhunia; Joseph M. Rifkind; Subroto Chatterjee (Molecular and Cellular Biochemistry, 1997)